2016
DOI: 10.1186/s12879-016-1470-x
|View full text |Cite
|
Sign up to set email alerts
|

Naïve-pooled pharmacokinetic analysis of pyrazinamide, isoniazid and rifampicin in plasma and cerebrospinal fluid of Vietnamese children with tuberculous meningitis

Abstract: Background: Among the various forms of TB, tuberculous meningitis (TBM) is the most severe, with about 30 % mortality and 50 % of survivors left with neurological sequelae. Children suffer more frequently from TBM than adults and outcomes are often poor due to difficulties in making the diagnosis and uncertainty regarding the best anti-tuberculosis drug regimen. The aim of this prospective study was to describe the pharmacokinetics of pyrazinamide, isoniazid and rifampicin in plasma and cerebrospinal fluid of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 49 publications
0
33
0
4
Order By: Relevance
“…Isoniazid is an important part of the first line treatment for TBM due to high early bactericidal activity within the first 2 days of treatment and its excellent CSF penetration . The CSF‐to‐plasma free concentration ratio (AUC total,CSF /AUC unbounded,plasma ) was estimated to be close to 1 (1.11) in the current study using a reported plasma protein binding of 14% .…”
Section: Discussionmentioning
confidence: 68%
“…Isoniazid is an important part of the first line treatment for TBM due to high early bactericidal activity within the first 2 days of treatment and its excellent CSF penetration . The CSF‐to‐plasma free concentration ratio (AUC total,CSF /AUC unbounded,plasma ) was estimated to be close to 1 (1.11) in the current study using a reported plasma protein binding of 14% .…”
Section: Discussionmentioning
confidence: 68%
“…The lung cavity and surrounding fibrosis, depending on the size, will create a physicochemical barrier to drug entry, leading to anatomical site-based monotherapy. Indeed, this differ ential penetration has also been identified in pericardial 194 and meningeal 195 tuberculosis.…”
Section: Pharmacokinetic Variability and Acquired Drug Resistancementioning
confidence: 71%
“…A recent study has investigated, in children with TBM, the CSF exposure to anti-tubercular drugs and found that at a dose of 10mg/kg, rifampicin levels are lower than the minimum inhibitory concentration of susceptible bacteria 32 . The reasons behind the low RIF exposure in this cohort are unknown, and whether HIV status is the driving force behind the low exposure has been a subject of debate as previously discussed in the introduction.…”
Section: Discussionmentioning
confidence: 99%